(3GdeMGSHI hGdMGSHGJ GdBdjI (B:s (3hjfOhR (B2000(3,hhQO(B2000(3,GcSd(B2000 /s - (3Gdajhej, eMeOs; (3eHGQc, UdGM GdOjf s ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3ebOe GdMGSH hfXGe GdJTZjd OhS, GdJYQja HGdMGSH hbOQJg hMOhO GSJNOGeg, HQfGeL GdMGSH, NUGFU HQfGeL hjfOhR (B2000(3, CSGSjGJ HQfGeL GcSd, OhQ (B2000 (3hJWHjbGJg GdGOGQjIs
Keywords: (3GdMGSHGJ GdGdcJQhfjI(B-(3HQGeLs; (3GdeMGSHIs